2017
DOI: 10.1186/s12942-017-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping outdoor habitat and abnormally small newborns to develop an ambient health hazard index

Abstract: BackgroundThe geography of where pregnant mothers live is important for understanding outdoor environmental habitat that may result in adverse birth outcomes. We investigated whether more babies were born small for gestational age or low birth weight at term to mothers living in environments with a higher accumulation of outdoor hazards.MethodsLive singleton births from the Alberta Perinatal Health Program, 2006–2012, were classified according to birth outcome, and used in a double kernel density estimation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Statistics Canada has reported that small newborns are increasing over time for our geographical areas of interest. 5 Nielsen et al 45 published on the spatial distribution of SGA and LBWT for the entire province but comparisons cannot be made due to methodological differences. As for ciSGA/ciLBWT, there are no published temporal trends for each city participating in the CNN to compare to.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics Canada has reported that small newborns are increasing over time for our geographical areas of interest. 5 Nielsen et al 45 published on the spatial distribution of SGA and LBWT for the entire province but comparisons cannot be made due to methodological differences. As for ciSGA/ciLBWT, there are no published temporal trends for each city participating in the CNN to compare to.…”
Section: Discussionmentioning
confidence: 99%
“…Over the five operational years of the project, the outcomes included development of a new algorithm; creation of an interactive visualization tool to visualize data mining results; identification of an initial list of potential hypotheses and a secondary list of robust hypotheses linking specific chemical pollutants mixtures with ABO. Additionally, the project had other 'side outcomes' such as new classification methods in DM [39], ABO and industrial pollutants maps [40], description of ABO and related risk factors' prevalence [41], testing the usefulness of existing publicly available data, learning about the collaborative process, and training a new generation of interdisciplinary researchers in environmental health.…”
Section: Research Outcomes and Knowledge Translationmentioning
confidence: 99%